Comparison of polyglycolic acid acupoint catgut embedding therapy monofilaments for a juvenile pseudo-myopia surface modified by two processing methods. Issue 19 (October 2019) - Fu, Shaoju; Lu, Yao; Zhang, Peihua
Polyglycolic acid (PGA) acupoint catgut embedding therapy (ACET) monofilament has been heavily used for juvenile pseudopia in the recent years. However, poor hydrophilicity and cytocompatibility have limited its development and wide practical application. In this context, this work is aimed to develop ACET materials with good comprehensive properties by surface modifications. Two different methods, namely ultrasound and plasma technologies, were selected to modify the surface property of PGA monofilaments to improve their wetting and compatibility with tissues, while minimizing degradation of the fibers. Moreover, the effects of these two processing methods on the structure, mechanical and in vitro properties of PGA were fully characterized. Both the ultrasound and plasma modified samples were observed to have a larger surface roughness, and their weights and diameters were decreased. Samples P-PGA1 (76.2° ± 1.4°) and P-PGA2 (73.5° ± 1.9°) exhibited the smallest contact angle values among their groups, respectively. The tensile properties and bending stiffness values of modified PGA decreased slightly, while their swelling ratios were greatly improved. All the prepared samples presented no toxicity (more than 75% cells being viable), and their cell attachment ratios (cultured for 48 h) were also enhanced. In summary, plasma and ultrasound modified PGA showed better hydrophilicity and in vitro properties compared to that of unmodified samples, while retaining the other excellent characteristics. These findings illustrated that the two processing methods were feasible and warrant further study in the application of ACET materials.